Serogroups and Neisseria meningitidis PORA, FETA and FHBP gene distribution in Vietnam from 2014 to 2024 - Trieu, Phi Long; Vo, Viet Cuong; Bui , Thi Lan Anh; Trinh, Van Toan; Bui , Thi Thanh Nga; Hoang, Dang Hieu; Hoang, Van Tong; Dong, Van Quyen; Nguyen, Huy Hoang (Vietnam Journal of Biotechnology, 2025)
Invasive meningococcal disease (IMD), caused by Neisseria meningitidis, is a continued public health concern. Invasive meningococcal disease, caused by Neisseria meningitidis, is a continued public health concern. Of the 12 N. meningitidis serogroups, the majority of invasive disease is caused by serogroups A, B, C, Y and W. This study aimed to investigate the serogroups, subgenotype, and fHbp antigenic profiles of N. meningitidis strains isolated in Vietnam from 2014 to 2023. Serogrouping of N. meningitidis by multiplex PCR assay and the genetic profiles including the porA, fHbp genes were analyzed using Sanger sequencing and bioinformatic methods. Of the 186 strain isolates, the most common serogroups were B (161 isolates, 86.6%), following serogroup B (5, 2.7%) and the remaining rates belongs to the other serogroups except serogroups A, B, C, W135, and Y. A total of 32 different combinations of VR1/VR2 PorA were identified in this study including 13 VR1 families and 21 VR2. The most common VR1 families were P1.22-25 (n = 36; 23.2%) followed by P1.7-2 (n= 31; 20.0%), P1.22 (n = 24; 15.5%), P1.22-11 (n = 19; 12.3%). As for VR2, the most frequent variants were 14 (n = 60, %), 15-25 (n = 20; 21.67%). The three most common profiles of porA gene were P1.22-25,14,36 (n = 24), P1.22,14,36 (n = 22), and P1.22-11,15-25,36 (n = 19). FHbp variant group 2 was most common (n = 142; 97.3%), followed by group 1 (n = 4; 2.7%), meaning a similar number of subfamily A (n = 142, being variant group 2) and B (n = 4, being variant group 1). 5 variants of subfamily A were found. The A22 variant was the most frequent (n = 52; 19.7%). On the basis of genotypic data showed poor matching the PorA and subfamily B FHbp component of the multicomponent 4CMenB Novartis meningococcal B vaccine.